1992
DOI: 10.1104/pp.98.4.1310
|View full text |Cite
|
Sign up to set email alerts
|

Internal CO2 Measured Directly in Leaves

Abstract: Observations of nonuniform photosynthesis across leaves cast doubt on intemal CO2 partial pressures (p) calculated on the assumption of uniformity and can lead to incorrect conclusions about the stomatal control of photosynthesis. The problem can be avoided by measuring pi directly because the assumptions of uniformity are not necessary. We therefore developed a method that allowed pi to be measured confinuously in situ for days at a time under growth conditions and used it to investigate intact leaves of sunf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(28 citation statements)
references
References 20 publications
3
24
0
1
Order By: Relevance
“…Wild-type rice plants under water stress displayed a reduction in stomatal conductance and an inhibition of photosynthetic activity and C assimilation. Lauer and Boyer (1992) demonstrated that, during drought stress, the limitation in C assimilation was due to the reduction of the biochemical capacity of photosynthesis. The authors showed that although a simultaneous reduction of stomatal opening occurred during water deficit, calculated substomatal CO 2 concentration (Ci) was maintained or even increased.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type rice plants under water stress displayed a reduction in stomatal conductance and an inhibition of photosynthetic activity and C assimilation. Lauer and Boyer (1992) demonstrated that, during drought stress, the limitation in C assimilation was due to the reduction of the biochemical capacity of photosynthesis. The authors showed that although a simultaneous reduction of stomatal opening occurred during water deficit, calculated substomatal CO 2 concentration (Ci) was maintained or even increased.…”
Section: Discussionmentioning
confidence: 99%
“…1). In the cup, the CO2 equilibrated with that in the stomatal pores adjacent to the airspace Lauer and Boyer, 1992;Boyer and Kawamitsu, 2011). The cup was connected in a closed loop with an IRGA (LI-840A; LI-COR) and a micro blower (109P0412H309; Sanyo Denki Co., Ltd., Osaka, Japan) which allows the air to gently circulate around the loop (ca.…”
Section: Plant Materialsmentioning
confidence: 99%
“…These are considered problems for the A Ci analysis, which usually depends on calculated Ci and thus the diffusive behavior of water vapor. Lauer and Boyer (1992) and Boyer and Kawamitsu (2011) considered the direct method to be a robust approach for tracing A Ci curves. In this study, we incorporated a direct Ci measurement system into the LI-6400 open gas exchange system (LI-COR, Lincoln, NE, USA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the decrease of photosynthesis under water stress can be associated with perturbations of the photochemical processes (Lauer & Boyer 1992, Yordanov et al 2003. In particular, photosystem II (PSII) is very sensitive to water stress, because it results in damage of the electron transport system linked to PSII (He et al 1995).…”
Section: Introductionmentioning
confidence: 99%